In-vitro validation of a new method to assess the clinical accuracy of complete arch impressions - Waldecker, Moritz; Schessler, Katherina; Bömicke, Wolfgang; Rammelsberg, Peter; Rues, Stefan (Clinical oral investigations, 2025)
To develop and validate a new method to acquire reference distances.
Online veröffentlicht: 25. Februar 2025
Gesehen am 08.10.2025